1996
DOI: 10.1164/ajrccm.153.4.8616571
|View full text |Cite
|
Sign up to set email alerts
|

Safety aspects of local endobronchial allergen challenge in asthmatic patients.

Abstract: Local endobronchial allergen challenge is being increasingly used to investigate the role of allergic inflammation in asthma. However, little information is available about the safety of this procedure and the changes induced in airway physiology. BAL and biopsy were performed at 10 min and at 4 to 6 h, or 24 h after segmental allergen challenge in 49 patients with atopic asthma. Two hours after challenge, FEV1 was reduced from 97.6 +/- 13.9 (mean +/- SD) to 83.4 +/- 21.7% predicted. FEV1 remained reduced at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
4
17
1
Order By: Relevance
“…1 Studies using the same models as in the current study reported a maximum of late-phase bronchoconstriction approximately 6 hours after allergen exposure. 3,13 This discrepancy does not support the concept that bronchoconstriction and eosinophil recruitment are directly related. 3,26 Indeed, there is evidence to question this concept.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1 Studies using the same models as in the current study reported a maximum of late-phase bronchoconstriction approximately 6 hours after allergen exposure. 3,13 This discrepancy does not support the concept that bronchoconstriction and eosinophil recruitment are directly related. 3,26 Indeed, there is evidence to question this concept.…”
Section: Discussionmentioning
confidence: 77%
“…11,12 Segmental allergen challenge has been widely used because of its safety and the possibility to compare BAL fluid and biopsy specimens from challenged and unchallenged segments intraindividually. 13 Most protocols include 2 bronchoscopies. The first bronchoscopy is performed during the early asthmatic response (5-10 minutes after challenge).…”
mentioning
confidence: 99%
“…Fibreoptic bronchoscopy, endobronchial allergen challenge and BAL were performed in accordance with our published procedure [23], conforming to current National Heart, Lung and Blood Institute (NHLBI) guidelines [24]. Premedication consisted of nebulized salbutamol 5 mg and ipratropium bromide 0.5 mg, intravenous atropine 0.6 mg, and intravenous midazolam as required (median 6.5 (range 0-8) mg).…”
Section: Fibreoptic Bronchoscopy and Endobronchial Allergen Challengementioning
confidence: 99%
“…Previous guidelines have suggested that an FEV 1 less than 60% constitutes a contraindication to performing research bronchoscopy (1). However, bronchoscopy in adults with asthma has been performed safely when the FEV 1 is lower, such as less than 50% predicted post-bronchodilator, and in patients with COPD (30,72,76) when the FEV 1 is less than 25% predicted prebronchodilator. Furthermore, in a single report, Martin and colleagues (22) demonstrated that bronchoscopy was safely performed in subjects with asthma with an FEV 1 less than 30% predicted.…”
Section: Safetymentioning
confidence: 99%
“…This is also generally well tolerated, although changes in lung function have been reported (76). BAL does not significantly alter airway responsiveness, airflow limitation, and/or airway inflammation when BAL is incorporated into other procedures, such as bronchial biopsy, and segmental or whole lung allergen challenge (71,(76)(77)(78)80).…”
Section: Safetymentioning
confidence: 99%